Optical induction in K0.5Na0.5NbO3 ferroelectric ceramic at low calcination temperature by sol-gel route. Issue 4 (1st November 2021) - Kumar, Shammi; Shandilya, Mamta; Thakur, Nagesh
Abstract: K0.5 Na0.5 NbO3 ceramic was synthesized at low calcination temperature by sol-gel route. Structural properties of ceramic were investigated by X-ray diffractometer, FESEM and FTIR spectrometer. Electro-optical properties of ceramic were investigated by UV-Vis and PL spectrometer. Dielectric nature of ceramic was studied at different frequencies and temperatures which disclosed that ceramic has maximum dielectric permittivity at 500 KHz. AC conductivity analysis shows negative temperature coefficient of resistance behavior. Leakage current was studied up to 180 V which shows low value of leakage current at room temperature. Ferroelectric nature was analyzed at different electric fields (5–20 kVcm −1 ) at 50 Hz.